QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia (Plant Physiology and Biochemistry, 2013)
Abstract Cork oak is an economically important forest species showing a great tolerance to high temperatures and shortage of water. However, the mechanisms underlying this plasticity are still poorly understood. Among the stress regulators, transcription factors (TFs) are especially important since they can control a wide range of stress-inducible genes, which make them powerful targets for genetic engineering of stress tolerance. Here we evaluated the influence of increasing temperatures (up to 55 °C) or drought (18% field capacity, FC) on the expression profile of an R2R3-MYB transcription factor of cork oak, the QsMYB1. QsMYB1 was previously identified as being preferentially expressed in cork tissues and as having an associated alternative splicing mechanism, which results in two different transcripts (QsMYB1.1 and QsMYB1.2). Expression analysis by reverse transcription quantitative PCR (RT-qPCR) revealed that increasing temperatures led to a gradual down-regulation of QsMYB1 transcripts with more effect on QsMYB1.1 abundance. On the other hand, under drought condition, expression of QsMYB1 variants, mainly the QsMYB1.2, was transiently up-regulated shortly after the stress imposition. Recovery from each stress has also resulted in a differential response by both QsMYB1 transcripts. Several physiological and biochemical parameters (plant water status, chlorophyll fluorescence, lipid peroxidation and proline content) were determined in order to monitor the plant performance under stress and recovery. In conclusion, this report provides the first evidence that QsMYB1 TF may have a putative function in the regulatory network of cork oak response to heat and drought stresses and during plant recovery.
From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 24161757
Keywords: Abiotic stress; Adaptation; Cork oak; Droughts; Gene expression; Gene Expression Regulation; Genes; Hot Temperature; Physiological; Plant; Plant Bark; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Quercus; Quercus: genetics; Quercus: metabolism; R2R3-MYB; Recovery; RNA Splicing; Stress; Transcription Factors; Transcription Factors: genetics; Transcription Factors: metabolism; water

Juvenile–adult tree associations in a continental Mediterranean ecosystem: no evidence for sustained and general facilitation at increased aridity - Granda, Elena; Escudero, Adrián; de la Cruz, Marcelino; Valladares, Fernando (Journal of Vegetation Science, 2012)
Question How do tree species identity, microhabitat and water availability affect inter- and intra-specific interactions between juvenile and adult woody plants? Location Continental Mediterranean forests in Alto Tajo Natural Park, Guadalajara, Spain. Methods A total of 2066 juveniles and adults of four co-occurring tree species were mapped in 17 plots. The frequency of juveniles at different microhabitats and water availability levels was analysed using log-linear models. We used nearest-neighbour contingency table analysis of spatial segregation and J-functions to describe the spatial patterns. Results We found a complex spatial pattern that varied according to species identity and microhabitat. Recruitment was more frequent in gaps for Quercus ilex, while the other three species recruited preferentially under shrubs or trees depending on the water availability level. Juveniles were not spatially associated to conspecific adults, experiencing segregation from them in many cases. Spatial associations, both positive and negative, were more common at higher water availability levels. Conclusions Our results do not agree with expectations from the stress-gradient hypothesis, suggesting that positive interactions do not increase in importance with increasing aridity in the study ecosystem. Regeneration patterns are species-specific and depend on microhabitat characteristics and dispersal strategies. In general, juveniles do not look for conspecific adult protection. This work contributes to the understanding of species co-existence, proving the importance of considering a multispecies approach at several plots to overcome limitations of simple pair-wise comparisons in a limited number of sites.
Keywords: faginea; Juniperus thurifera; patterns; Pinus nigra; Quercus; Quercus faginea; Quercus ilex; Regeneration; spatial; spatial patterns; Stress-gradient hypothesis; water; Water availability

Adsorption equilibria of water vapor on cork. - Lequin, Sonia; Chassagne, David; Karbowiak, Thomas; Gougeon, Régis; Brachais, Laurent; Bellat, Jean-Pierre (Journal of agricultural and food chemistry, 2010)
We report here for the first time a complete thermodynamic study of water vapor adsorption on crude cork powder and plate. Adsorption-desorption isotherms were accurately measured by thermogravimetry at 283, 298, and 313 K in a large range of relative pressure. Adsorption enthalpies were determined by calorimetry as a function of loading. Adsorption-desorption isotherms exhibit a hysteresis due to the swelling of the material. The influence of the presence of lenticels on the adsorption properties of cork is found to be negligible. A detailed analysis and interpretation of adsorption data allow proposal of an adsorption mechanism in two steps. (i) First, water adsorbs on hydrophilic sites constituted by hydroxyl and methoxyl groups. (ii) Then water adsorption continues by clusters formation around the hydrophilic sites.
The following values have no corresponding Zotero field: accession-num: 20192215
Keywords: Adsorption; Plant Bark; Plant Bark: chemistry; Quercus; Quercus: chemistry; Thermodynamics; water; Water: chemistry

Geophysical imaging of root-zone, trunk, and moisture heterogeneity - Attia Al Hagrey, Said (Journal of Experimental Botany, 2007)
The most significant biotic and abiotic stress agents of water extremity, salinity, and infection lead to wood decay and modifications of moisture and ion content, and density. This strongly influences the (di-)electrical and mechanical properties and justifies the application of geophysical imaging techniques. These are less invasive and have high resolution in contrast to classical methods of destructive, single-point measurements for inspecting stresses in trees and soils. This review presents some in situ and in vivo applications of electric, radar, and seismic methods for studying water status and movement in soils, roots, and tree trunks. The electrical properties of a root-zone are a consequence of their moisture content. Electrical imaging discriminates resistive, woody roots from conductive, soft roots. Both types are recognized by low radar velocities and high attenuation. Single roots can generate diffraction hyperbolas in radargrams. Pedophysical relationships of water content to electrical resistivity and radar velocity are established by diverse infiltration experiments in the field, laboratory, and in the full-scale ‘GeoModel’ at Kiel University. Subsurface moisture distributions are derived from geophysical attribute models. The ring electrode technique around trunks images the growth ring structure of concentric resistivity, which is inversely proportional to the fluid content. Healthy trees show a central high resistivity within the dry heartwood that strongly decreases towards the peripheral wet sapwood. Observed structural deviations are caused by infection, decay, shooting, or predominant light and/or wind directions. Seismic trunk tomography also differentiates between decayed and healthy woods.
10.1093/jxb/erl23710.1093/jxb/erl237The following values have no corresponding Zotero field: accession-num: 17229759
Keywords: Electric Impedance; Electrical resistivity techniques; Electrodes; Geological Phenomena; Geology; Plant Roots; Plant Roots: metabolism; Populus; Populus: physiology; Portugal; Quercus; Quercus: anatomy & histology; Quercus: metabolism; Radar; radar imaging; ring electrode array; root-zone; sap flow; seismic tomography; trunk ring structure; vadose zone; water; water content; water flow; Water: analysis; Water: metabolism

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G.; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)The following values have no corresponding Zotero field: accession-num: 16356909
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology